A potential study on clove oil, eugenol and eugenyl acetate as diesel fuel bio‐additives and their performance on one cylinder engine - Kadarohman, Asep; ​, Hernani; Khoerunisa, Fitri; Astuti, Rizki M. (Transport, 2010)
Research on the potency of essential oils as diesel fuel bio-additives has been reported. It also has been found out that clove oil has a better performance than turpentine oil on decreasing Break Specific Fuel Consumption (BSFC) and reduces the exhaust emissions of the engine. Clove oil is essential oil the content of which is made of eugenol acting as the main component. Eugenol has a bulky structure, two oxygen atoms and can form eugenyl acetate from ester reaction. Eugenyl acetate has a bulkier structure and higher oxygen content than eugenol which leads to optimizing the process of fuel combustion. This experiment can give information about the potency of the bio-additive based on clove oil and eugenol and about the influence of oxygen enrichment with eugenol on the performance of the diesel fuel bio-additive. In general, this experiment covered three stages. The first step is the characterization of the diesel fuel bio-additive using a GCMS and FTIR spectrophotometer. The second step is the characterization of the diesel fuel bio-additive and composition optimization. The final step is conducting a diesel fuel bio-additive performance test on one cylinder engine on a laboratory scale. The results of the carried out experiment show that clove oil, eugenol and eugenyl acetate can decrease Break Specific Fuel Consumption (BSFC) and reduce the exhaust emissions of the engine as well as oxygen enrichment can help in reaching optimal fuel combustion. First published online: 27 Oct 2010